2011
DOI: 10.1371/journal.pmed.1001116
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Attenuates the Influence of FTO Variants on Obesity Risk: A Meta-Analysis of 218,166 Adults and 19,268 Children

Abstract: Ruth Loos and colleagues report findings from a meta-analysis of multiple studies examining the extent to which physical activity attenuates effects of a specific gene variant, FTO, on obesity in adults and children. They report a fairly substantial attenuation by physical activity on the effects of this genetic variant on the risk of obesity in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
453
6
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 483 publications
(515 citation statements)
references
References 38 publications
42
453
6
8
Order By: Relevance
“…These fi ndings contrast with at least three studies which report no associations with energy intake in children (Hakanen et al, 2009;Okuda et al, 2011;Stutzmann et al, 2009) and to the observation in mice that FTO may modulate energy homeostasis through energy expenditure (Fischer et al, 2009;Speakman, 2010). However, several studies, including a large meta-analysis have recently shown that energy expenditure through activity appears to attenuate the genetic susceptibility to overweight and obesity from FTO in children Scott et al, 2010) and adults (Andreasen et al, 2008;Kilpelainen et al, 2011).…”
Section: Fat Mass and Obesity Associated Gene And Eating Behaviourcontrasting
confidence: 68%
“…These fi ndings contrast with at least three studies which report no associations with energy intake in children (Hakanen et al, 2009;Okuda et al, 2011;Stutzmann et al, 2009) and to the observation in mice that FTO may modulate energy homeostasis through energy expenditure (Fischer et al, 2009;Speakman, 2010). However, several studies, including a large meta-analysis have recently shown that energy expenditure through activity appears to attenuate the genetic susceptibility to overweight and obesity from FTO in children Scott et al, 2010) and adults (Andreasen et al, 2008;Kilpelainen et al, 2011).…”
Section: Fat Mass and Obesity Associated Gene And Eating Behaviourcontrasting
confidence: 68%
“…It is well known that the association of FTO variants with BMI is observed more frequently in sedentary teenagers (16,17,47). In this population, the FTO gene showed an association in young people to the obesogenic factor of the time spent watching television and playing video games, as has occurred in other populations (17,43,48). We found a significant association between BMI and sedentary lifestyle, even after adjustment for physical activity.…”
Section: Discussionsupporting
confidence: 65%
“…The obesityassociated single nucleotide polymorphisms (SNP) are located in intron 1 of the FTO, all of which fall in a region of strong linkage disequilibrium (14); FTO encodes a protein that repairs alkylated DNA and RNA by oxidative demethylation (15); it has been implicated in increasing energy intake by regulating the expression of the genes that control appetite, such as leptin, leptin receptor, and neuropeptide Y (16). FTO has been associated with the modification of the degree of obesity in response to physical activity (17).…”
mentioning
confidence: 99%
“…1,2 The cause of obesity is multifactorial, for which genetics, environment, socioeconomic status, culture, and ethnicity are some primary factors. 3,4 Thus, the pathophysiology of obesity is a result of a complex interaction between environmental and genetic factors 5,6 that still are not fully delineated and understood. Obesity is defined as a body mass index (BMI) $30 and overweight as a BMI $25 in adults.…”
Section: Discussionmentioning
confidence: 99%